Realizer-functionalism and Life After Death - Mahdi Ghiasvand (پژوهشنامه فلسفه دین, 2019)
In contemporary philosophy of mind, some have tried to reduce mental states to physical and bodily states by proposing a model that draws upon both functionalism and the identity theory; thus, reducing the human person to his/her physical body and nervous system. On the one hand, this approach, often dubbed “reductive functionalism” or “identity functionalism”, can be considered a developed and revised version of the identity theory; on the other hand, due to being a version of functionalism, it has been sometimes called “realizer-functionalism”. In this article, it has been argued that defending the possibility of life after death based upon this approach, has almost no advantages over other physicalistic formulations of the possibility of life after death; since in order to avoid an internal inconsistency, it transforms into a version of either type or token identity theory; and thus fails to employ concepts like “realization” in order to explain the person-body relation and the multiple realizability of the person.